The Effect Of Transformasional Leadership And Training On Internal Service Quality With Organizational Culture As A Mediation Variable - Manggala, Istiqlal Wiranata; Nurhayati, Mafizatun (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to analyze the factors that influence the quality of internal service at Burger King FSDT in South Jakarta. The population of this research is employees of Burger King FSDT in South Jakarta with a total sample of 126 employees. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of the study found that transformational leadership has a positive and significant effect on organizational culture. Transformational leadership has no effect on the quality of internal services. Organizational culture has a positive and significant effect on the quality of internal services. Training has a positive and significant effect on organizational culture. Training does not affect the quality of internal services. Organizational culture is not able to mediate between transformational leadership variables and internal service quality. Organizational culture is able to mediate between training variables and internal service quality.